Exhumation-Can Dead Tell Tales? - MUHAMMAD KASHIF BUTT, MARIAM ARIF, MUHAMMAD MAQSOOD (Journal of Fatima Jinnah Medical University, 2018)
Exhumation means legal digging a dead body out of a grave buried in a legitimate fashion done by the court order under section 176 CrPC, not applicable to retrieval of dead bodies buried by criminals illegally. Exhumation is done for a number of reasons including determination of cause of death and establishment of identity in unnatural deaths. The present study was aimed to collect data of 32 exhumed cases conducted through KEMU by the judicial orders during 2011-13 and to evaluate the success rate of exhumation on the basis of morphological and toxicological findings. There were 25 males (78.1%) and 7 females (21.8%) showing male preponderance during third decade of life. The interval between burial and exhumation was within six months in 28 cases (87.5%) revealing a mean postmortem interval of 6.9 months. In the present study, the cause of death at exhumation could be clearly determined in 13 cases (40.6%) on the basis of fracture of bones or poisoning while in 19 cases (59.3%), it remained undetermined. Manner of burial and postmortem interval are major determining factors of the possible outcome of exhumation.